Comparison of the FEMA P-154 Methodology with Seismic Analysis in the “Galería Tradición” of Cercado de Lima - Lenin Bendezú, R. (2025)
The seismic vulnerability of buildings with considerable age represents a crucial challenge for urban resilience in a historic city like Lima. In this research, a sample of 30 publicly accessible galleries within the Cercado de Lima was evaluated. These structures were built with now-obsolete structural systems and are subject to deteriorated conditions. The FEMA P-154 methodology was applied to conduct rapid visual inspections and to classify the structures according to their level of seismic vulnerability based on the score established by the format. Additionally, a gallery with a critical FEMA score was selected for structural modeling in ETABS using previously scaled historical seismic records, following the guidelines of the E.030 Seismic Design Code. A Schmidt hammer test was also conducted to estimate the concrete strength of the selected building. The results show that more than one-third of the buildings exhibit high vulnerability and that the drifts obtained in the dynamic analysis exceed the limits established by the E.030 code. The FEMA P-154 methodology proved to be an effective tool for prioritizing structural interventions in urban contexts with limited resources.